Acceleration of Sperm Transit Time and Reduction of Sperm Reserves in the Epididymis of Rats Exposed to Sibutramine - Bellentani, Fernanda F. [UNESP]; Fernandes, Glaura S. A.; Perobelli, Juliana E.; Pacini, Enio S. A. [UNESP]; Kiguti, Luiz R. A. [UNESP]; Pupo, Andre S. [UNESP]; Kempinas, Wilma D. G. [UNESP] (Amer Soc Andrology, Inc, 2011)
Sibutramine is a drug globally used for the treatment of obesity. The aim of this study was to investigate male reproductive disorders caused by sibutramine in adult rats. Wistar rats were treated for 28 consecutive days (gavage) with 10 mg/kg of sibutramine. Control animals received only vehicle (dimethylsulfoxide and saline). The rats were sacrificed for evaluation of body and reproductive organ weights, sperm parameters, hormone levels (luteinizing hormone, follicle-stimulating hormone, and testosterone), testicular and epididymal histopathology, sexual behavior, fertility and in vitro contractility of the epididymal duct. Sibutramine decreased (P < .05) weights of the epididymis and ventral prostate, but not of other reproductive organs. The sperm number and transit time in the epididymal cauda were decreased (P < .001), but the daily sperm production was not altered. Moreover, morphology and sperm motility, histopathology of the testes and epididymis, sexual behavior, fertility, and serum hormone levels were not altered by the treatment. Sibutramine increased the potency of norepinephrine and, per se, increased the mechanical activity of the epididymal duct in vitro. Thus, although sibutramine in these experimental conditions did not interfere with the reproductive process of rats, it provoked acceleration of the sperm transit time and a decrease in the sperm reserves in the epididymal cauda. This alteration is probably related to the sympathomimetic effect of this drug, as shown by the in vitro assays. In humans, use of this drug might present a threat for male fertility because sperm reserves in men are naturally lower than those in rats.
Keywords: Male rats; sympathetic innervation